2020
DOI: 10.1097/bsd.0000000000000970
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Spondylolisthesis

Abstract: Study Design: A prospective cohort. Objective: The objective of this study was to develop a scoring system for lumbar degenerative spondylolisthesis (LDS) that would guide decision-making. Background: The management protocol for LDS has been under debate, with no guidelines. Most studies oversimplify LDS as a homogenous entity. Materials and Methods: A retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…They protect the disk from excessive shear and rotation, whilst guiding motion between two adjacent vertebrae 30. An association between sagittal orientation of the lumbar facet joints and LDS have been proposed by previous studies 6,14,31–33. According to Boden et al 14 the threshold for sagittal oriented lumbar facet joints are 45° at L4/L5.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…They protect the disk from excessive shear and rotation, whilst guiding motion between two adjacent vertebrae 30. An association between sagittal orientation of the lumbar facet joints and LDS have been proposed by previous studies 6,14,31–33. According to Boden et al 14 the threshold for sagittal oriented lumbar facet joints are 45° at L4/L5.…”
Section: Discussionmentioning
confidence: 88%
“…30 An association between sagittal orientation of the lumbar facet joints and LDS have been proposed by previous studies. 6,14,[31][32][33] According to Boden et al 14 the threshold for sagittal oriented lumbar facet joints are 45°at L4/L5. We confirm that sagittal oriented facet joints are predictive of radiographic instability.…”
Section: Facet Joint Anglementioning
confidence: 99%
“…He suggested that patients older than 70 years are more likely to undergo decompression without fusion because older patients tend to suffer from comorbidities, making them less tolerant of a fusion procedure. 13 Schneider et al 27 also showed that patient age was associated with the decision for fusion. In our population, there was no difference in age between both groups.…”
Section: Demographic and Clinical Factorsmentioning
confidence: 99%
“…11,12 DA has been described as an alternative to fusion and an effective procedure, especially for patients without segmental hypermobility on dynamic lumbar radiographs. 13,14 In this context, it is a clinical challenge to identify the subgroup of patients who may benefit from an isolated decompression. Various factors might be considered when deciding whether to fuse, including patient demographics, symptom presentation, and radiographic parameters.…”
mentioning
confidence: 99%
“…Choice of surgical approach for LDS continues to be multifactorial, with significant controversy regarding not only decompression vs the addition of fusion but also regarding the ideal surgical approach. One group has implemented the use of a scoring system that includes clinical, radiographic, and technical variables to assist with tailoring the decision to add fusion to individual patients, 16 although this paradigm is not yet widely used. There is a need for continued study of the various fusion procedures with long-term outcomes to develop a more comprehensive set of guidelines for treating LDS.…”
mentioning
confidence: 99%